A rare case of renal thrombotic microangiopathy associated with Castleman's disease. Issue 1 (December 2017) - Mutneja, Anubha; Cossey, L.; Liapis, Helen; Chen, Ying
Abstract Background Castleman's disease (CD) is an uncommon, heterogeneous lympho-proliferative disorder leading to high circulating levels of interleukin-6 (IL-6) and vascular endothelial growth factor (VEGF). Renal involvement has been only described in a limited number of small studies. Herein, we report a rare case of renal thrombotic microangiopathy (TMA) associated with CD and investigate the podocyte expression of VEGF in the renal biopsy prior to initiation of treatment. Case presentation An 18-year-old male presented with fever, diarrhea, diffuse lymphadenopathy, ascites and acute kidney injury. Laboratory tests for hemolytic uremic syndrome and thrombotic thrombocytopenic purpura were negative. The kidney biopsy showed TMA. An excisional lymph node biopsy was consistent with CD, plasma cell variant. Immunofluorescence staining showed suppressed podocyte VEGF expression. Chemotherapy that inhibits production of inflammatory mediators including IL-6 and VEGF led to complete recovery of renal function. Conclusions Our case illustrates a rare renal histological feature of CD. IL-6 and VEGF are postulated to suppress glomerular VEGF expression, thereby causing renal TMA. Therapy directed against these inflammatory mediators may have important therapeutic implications.